Three decades of development crises in Nigeria : essays - Onosode, G. O. (Marina, Lagos : Malthouse, 1993)
The essays contained in this volume have been assembled without being edited to achieve internal consistency. That this has been accomplished by the publishers without some embarrassment to the author indicates the extent to which his views on fundamental issues remained "in Context" unchanged throughout the first three decades of development effort in post-independence Nigeria.
Includes index.
rpm 21/03/2018, ijb 04/02/2019
Loans
Keywords: Economic development; Economic condition; Nigeria